2021
DOI: 10.1364/osac.433758
|View full text |Cite
|
Sign up to set email alerts
|

Performance study of a highly sensitive plasmonic sensor based on microstructure photonics using an outside detecting method

Abstract: In this article, we design a microstructure based photonic crystal fiber (PCF) with external sensing surface plasmon resonance (SPR) sensor. The performance of the design is numerically evaluated incorporating the finite element method (FEM) with Perfectly Matched Layer (PML) boundary condition of scattering case. Modal analysis is performed using finer mesh analysis. At the optimized thickness (40nm) of chemically stable gold (Au) layer, the ever been maximum reported wavelength sensitivity (WS) and standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…This was also confirmed by many researchers in their study as reported by Sakib et al, they varied the thickness of the gold layer in the range of 30 nm, 40 nm and 50 nm. Confinement loss at 50 nm gold thickness has a small confinement loss value (Sakib et al, 2021), the same results have also been reported by Rahman et al, with variations in gold thickness of 25 nm, 30 nm, 40 nm, and 50 nm. that the thicker the gold layer the smaller the confinement loss value (M. T. .…”
Section: Figure 2 Real Relation Of Refractive Index Vs Confinement Losssupporting
confidence: 87%
“…This was also confirmed by many researchers in their study as reported by Sakib et al, they varied the thickness of the gold layer in the range of 30 nm, 40 nm and 50 nm. Confinement loss at 50 nm gold thickness has a small confinement loss value (Sakib et al, 2021), the same results have also been reported by Rahman et al, with variations in gold thickness of 25 nm, 30 nm, 40 nm, and 50 nm. that the thicker the gold layer the smaller the confinement loss value (M. T. .…”
Section: Figure 2 Real Relation Of Refractive Index Vs Confinement Losssupporting
confidence: 87%